Evaluating Nigella sativa meal (black cumin meal) in lamb diets and its impact on the growth performance, digestion coefficient of nutrients, nitrogen balance and rumen fermentation - Eldeeb, Fares A.; Abdel-Raheem, Ghada S.E; Abdelazeem, Shimaa; Nasr, Heba A. (Journal of Advanced Veterinary Research, 2026)
The purpose of this study was to evaluate the effects of adding Nigella sativa meal (NSM) at varying levels on the performance of growth, digestibility of nutrients, nitrogen balance and rumen fermentation of growing lamb. Thirty-five Rahmani lambs were divided into five groups at random for 90 days. NSM was added to the diets of lambs at 0%, 6%, 12%, 18% and 24% for G1 (control), G2, G3, G4 and G5, respectively. The parameters measured were weight gain, feed consumption, digestibility of nutrients, nitrogen balance, and rumen fermentation. Lambs fed with NSM diets had significantly higher weight gain, feed intake, and feed efficiency compared with the control group. Nutrient digestibility like dry matter, crude protein, fat, fiber, and carbohydrates were improved with the addition of NSM. Rumen values revealed increased ammonia and volatile fatty acid concentrations, with reduced protozoa and bacterial numbers. It could be concluded that, the inclusion of 18% NSM proved to be the most effective in enhancing final weight, nutrient digestibility, and rumen function.